Daily fatigue among patients with symptomatic osteoarthritis: A cross-sectional study in Mosul city - K. Mohialdeen, Ali; S. Thabit, Zahraa (Public Health of Indonesia, 2025)
Background: Osteoarthritis is one of the most common type of arthritis disability and bad quality of life. OA is the disease that occur in older people or even in middle age people that its severity increases with age. Also, it associated with many trigger factors as genetics, occupation, and obesity. Objectives: to identify the sociodemographic, physical, emotional, and disease-related factors that influence fatigue in people with symptomatic osteoarthritis, the authors conducted a study on the relationship between fatigue and symptomatic OA. Methods: a cross-sectional study design was archived to group of patients was suffering from osteoarthritis. The American College of Rheumatologists' criteria were used to diagnose 306 participants in this study who were 45 years of age or older. While a portion of the Knee injury and Osteoarthritis Outcome Score (KOOS) scale was utilized to evaluate the signs and symptoms of osteoarthritis, the fatigue ((Facit- Version 4) scale was employed to measure severity of fatigue among these patients. Results: the mean 50.04±8.23 females had a higher prevalence of 249 (81.4%), with odema showed 101 (33.0%) while the usually crepitus exhibited 143 (46.7%). The stiffness was illustrated higher percent in usually stiffness in 107 (35%) in other hand morning stiffness was showed moderate stiffness in 127 (41.5%) and rest stiffness was demonstrated sever rest stiffness in 131 (42.8%). The ability of the knee extension was exhibited high percent in all times 96 (31.4%), in some time the rarely ability of knee bending in 101 (30%). The daily frequency of pain was showed high value 129 (42.2%) whereas the moderate change life style was showed 131 (42.8%) and finally there is moderate knee difficulty in 154 (50.3%). all symptoms that included in this study as odema, crepitus, stiffness in rest, in morning and all-time stiffness, disability of knee extension and knee bending, difficulty of knee, and frequently of pain exhibited the significant difference with fatigue score with p value ≤0.001. The change lifestyle was demonstrated significant different with fatigue scale score in p value ≤0.001. Conclusion: Patients with symptomatic OA, including pain, crepitus, stiffness especially in morning, in rest, night stiffness, both inability of knee extension, and knee bending, odema and difficulties of knee, may exhibit more sever fatigue. while the change lifestyle may decrease the severity of fatigue.